Evektivitas Media Sort Card pada Pembelajaran SKI di Kelas XI Agama MA Takhassus Al-Qur’an Wonosobo - Adiningsih, Rofikotun Wahyu; Khoiri, Ahmad; Aziz, Noor (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research aims to achieve the following objectives: 1) To explore the concept of Sort Card media in SKI Learning; 2) To examine the implementation of Sort Card media in SKI learning at Ma Takhassus Al-Qur'an Wonosobo; 3) To assess the effectiveness of using Sort Card media in SKI learning at Ma Takhassus Al-Qur'an Wonosobo. This research uses a descriptive qualitative field research approach to comprehensively present or elucidate an event or phenomenon. Qualitative research emphasizes the quality of data over quantity, gathered from interviews, direct observation, and relevant official documents rather than questionnaires. This approach focuses more on the process rather than the end result. The researcher serves as the primary instrument in data collection, utilizing multiple techniques simultaneously and analyzing data through an inductive or qualitative lens. The outcomes of qualitative research emphasize understanding meaning. This type of research is considered broad in scope as it explores the backgrounds, current conditions, and social interactions of individuals, groups, institutions, or society. Hence, researchers must engage directly in the field to study phenomena as they occur. Based on this research, it can be concluded that: 1) Understanding the concept of Sort Card media in SKI Learning; 2) Exploring the implementation of Sort Card media in SKI learning at Ma Takhassus Al-Qur'an Wonosobo; 3) Evaluating the effectiveness of Sort Card media in SKI learning at Ma Takhassus Al-Qur'an Wonosobo.